Wireless sensor network for landslide monitoring - Motakabber, S. M. A.; Ibrahimy, Muhammad Ibn; Anwar, Farhat (2013)
E very year all over the world many lives and properties are lost due to many geological catastrophes like, landslide or landslip. Manual and electronic monitoring systems are used for predicting the landslide. The m anual monitoring syst em is laborious and not practical. And most of the electronic systems are complex and expensive. A wireless sensor network in conjunction with a n underground pretension cable with a strain gage sensor attached at one end is proposed for a simple landslide monitoring system . A mathematical model has been developed for the system and the model is verified by simulation. The result shows that an early prediction of the landslide is possible by using the developed system .